Motivasi Kerja, Kepuasan Kerja, Dan Kinerja - Surwanti, Arni (208-7721)
Managing people in the workplace is an integral partof the management process. To understandthe importance of people in an organization is to recognize that the person is an element of an organization.An effective organization is an organization that will always ensure that the spirit of cooperation and commitment and a sense of satisfaction in employees. In order to make employees satisfied and committed to their work. Based on the results observed in several studies as described in this article have not shown consistent results, and the lack of clarity constructs related to motivation, satisfaction and performance, and a greater variety of variables that may moderate between satisfaction and performance. The findings of several studies relating to motivation, job satisfaction and performance, the results of research that shows motivation, satisfaction and performance possible is highly dependent on certain conditions, such as differences in personal needs, values, attitudes, interests and ability his task. Based on the characteristics of the job, there are some aspects of the job positions that impose limits or opportunities. Various practices of organization such rules, human resources policies, managerial policy, organizational reward system, as well as the factors interaction among employees that will affect the performance of the employees.